Contextualizing Breast Implant Removal Patterns with Google Trends: Big Data Applications in Surgical Demand. Issue 1 (January 2022) - Tian, William M.; Rames, Jess D.; Blau, Jared A.; Taskindoust, Mahsa; Hollenbeck, Scott T.
Abstract : Background: The demand for breast implant removal (BIR) has increased substantially in recent years. This study leveraged large datasets available through Google Trends to understand how changes in public perception could be influencing surgical demand, both geographically and temporally. Methods: Using Google Trends, we extracted relative search volume for BIR-related search terms in the United States from 2006 to 2019. A network of related search terms was established using pairwise correlative analysis. Terms were assessed for correlation with national BIR case volume based on annual reports provided by the American Society of Plastic Surgeons. A surgical demand index for BIR was created on a state-by-state basis. Results: A network of internally correlated BIR search terms was found. Search volumes for such terms, including "explant" [ρ = 0.912], "breast implant removal" [ρ = 0.596], "breast implant illness" [ρ = 0.820], "BII" [ρ = 0.600], and "ALCL" [ρ = 0.895] ( P < 0.05), were found to be positively correlated with national BIR case volume, whereas "breast augmentation" [ρ = -0.596] ( P < 0.05) was negatively correlated. Our 2019 BIR surgical demand index revealed that Nevada, Arizona, and Louisiana were the states with the highest BIR demand per capita. Conclusions: Google Trends is a powerful tool for tracking public interest and subsequently, online health information seeking behavior. There are clear networks of related Google search terms that are correlated with actual BIR surgical volume. Understanding the online health queries patients have can help physicians better understand the factors driving patient decision-making.